2006
DOI: 10.1590/s0104-42302006000200021
|View full text |Cite
|
Sign up to set email alerts
|

A síndrome da estafa profissional em médicos cancerologistas brasileiros

Abstract: Burnout syndrome is frequent among Brazilian cancer physicians and further studies should be conducted to evaluate its prevalence and prevention among other sub specialists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1
50

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 7 publications
3
16
1
50
Order By: Relevance
“…In a study of 1,000 American oncologists, Whinppen and Canellos (1991) 46 found that 56% of those investigated were suffering from some degree of burnout. Grunfels et al (2000), 48 Diaz and Stella (2006) 44 31 in Canada, Argentina and Brazil, respectively, obser ved lower burnout prevalence rates than in our study, using the same criteria adopted here. It is therefore to be concluded that these intensive care physicians had a greater prevalence of burnout than obser ved within other medical specialties and among physicians in other countries.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In a study of 1,000 American oncologists, Whinppen and Canellos (1991) 46 found that 56% of those investigated were suffering from some degree of burnout. Grunfels et al (2000), 48 Diaz and Stella (2006) 44 31 in Canada, Argentina and Brazil, respectively, obser ved lower burnout prevalence rates than in our study, using the same criteria adopted here. It is therefore to be concluded that these intensive care physicians had a greater prevalence of burnout than obser ved within other medical specialties and among physicians in other countries.…”
Section: Discussionsupporting
confidence: 68%
“…Since there is no consensus in the literature on how to interpret the MBI, we chose to describe the results both according to the criteria used by Ramirez et al and also according to the criterion used by Grunfeld et al (apud Tucanduva et al, 2006). 31 The first of these studies defined professional burnout as all three dimensions scored in the severe zone, whereas Grunfeld considers that if any of the dimensions are scored as severe, then burnout is present, irrespective of which dimension.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prevalência do sexo feminino entre pediatras também foi observada nos estudos de Menegaz (2004) 11 15 , em pesquisa com profissionais de Enfermagem, não constataram a presença da síndrome. 16 ; alto em exaustão e despersonalização e baixo em reduzida realização profissional por Lee et al (2008) 22 ; e médio nas duas primeiras e alto na última por Pérez et al (2011) 23 . Para Tucunduva et al (2006) 16 , a estafa profissional afeta um em cada dois médicos do mundo, sendo um terço deles atingidos de forma relevante e um décimo de forma severa, com características irreversíveis.…”
Section: Discussionunclassified
“…Desde então, aparece na literatura um grande volume de trabalhos que buscam identificar as fontes de estresse e seus efeitos nos MR e na qualidade da assistência prestada aos pacientes. Como fatores estressantes são apontadas a fadiga pela grande carga de trabalho, que desperta sentimentos hostis em relação a vivências de exploração e desrespeito, a falta de tempo para a vida pessoal, a privação do sono, a responsabilidade no atendimento aos pacientes, que traz o medo de cometer erros, e a falta de conhecimento e experiência, que ameaça a autoconfiança [20][21][22] .…”
Section: Maria Teresa Aquino De Campos Velho Et Alunclassified